Cyber forensics: from data to digital evidence - Marcella, Albert J. (Wiley corporate F&A, 2012)
"An explanation of the basic principles of data. This book explains the basic principles of data as building blocks of electronic evidential matter, which are used in a cyber forensics investigations. The entire text is written with no reference to a particular operation system or environment, thus it is applicable to all work environments, cyber investigation scenarios, and technologies. The text is written in a step-by-step manner, beginning with the elementary building blocks of data progressing upwards to the representation and storage of information. It inlcudes practical examples and illustrations throughout to guide the reader"--